Spouses' experience of living with a partner diagnosed with a dementia: a synthesis of the qualitative research. (11th January 2016) - Pozzebon, Margaret; Douglas, Jacinta; Ames, David
ABSTRACT: Background: The majority of people diagnosed with a dementia live at home with the support of their spouse. While this situation has advantages, it brings many challenges for the spouse, particularly dealing with the emotional impact of the behavioral changes associated with the dementia. A growing body of qualitative research has focused on understanding the spousal caregiver perspective of living with a partner diagnosed with dementia. The aim of this study was to complete a synthesis of the results of published qualitative studies that have explored the spousal experience. Method: An electronic database search of Ovid Medline, CINAHL, EMBASE, and PsychINFO from January 1980 to September 2014 was conducted. Sixteen studies met the inclusion criteria. Verbatim quotes of the participant interview data derived from these studies were collated and a thematic analysis was conducted. Results: Synthesis of the published data revealed five major themes. The theme of "loss of partner" was central, and around this central experience spouses described various processes: acknowledging change, being in crisis, adapting and adjusting, accepting and moving forward. Conclusions: These findings provide insights into the day-to-day adjustments and experiences of spousal caregivers whilst highlighting the importance of considering the impact of cognitive decline and dementia in a social-relational context.